Effects of Milk or Soy Milk Combined with Mild Resistance Exercise on the Muscle Mass and Muscle Strength in Very Old Nursing Home Residents with Sarcopenia - Feng-YI Chiang (MDPI AG, 2021)
Background and aims: Sarcopenia is recognized as a major public health issue, because it is prevalent in the elderly, especially those who live in long-term care facilities. The purpose of this study was to investigate the beneficial effects of milk or soy milk combined with resistance exercise on the muscle mass and muscle strength of individual elderly nursing home residents with sarcopenia. Methods: This study was a randomized controlled trial (clincaltrials.gov as NCT05035121) that recruited very old (>75 years) subjects with sarcopenia in a nursing home (Su-Ao and Yuanshan Branches, Taipei Veterans General Hospital) from June to December 2017. Thirty-five elderly (84.9 ± 6.1 years old) subjects were recruited and divided into three groups: control (n = 12), milk supplemented (n = 12), and soy milk supplemented (n = 11). All participants joined a mild resistance exercise training program three times a week (30 min/time). Moreover, elderly subjects in the milk and soy milk groups drank 200 mL of milk or soy milk for breakfast and as a snack after exercise. Results: After 12 weeks, compared to the baseline, calf circumferences had significantly increased in the control and soy milk groups (p = 0.0362 and p = 0.0197, respectively). Hand grip strength had significantly improved in the milk and soy milk groups (p = 0.0407 and p = 0.0096, respectively). In addition, there was no difference among the three groups. Conclusions: Mild resistance exercise combined with milk or soy milk improved the calf circumference and hand grip strength in very old nursing home residents with sarcopenia.